2021
DOI: 10.1039/d0sc04856a
|View full text |Cite
|
Sign up to set email alerts
|

Designed alpha-helical barrels for charge-selective peptide translocation

Abstract: Synthetic alpha-helix based pores for selective sensing of peptides have not been characterized previously. Here, we report a large transmembrane pore, pPorA formed from short synthetic alpha-helical peptides of tunable...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…Redesigned peptide nanopores have demonstrated that such transmembrane peptides stably form pores with a certain number of monomers, opening the field of peptide nanopores and providing promising nanopore-forming peptides to date. Recently, the Mahendran group reported that DpPorA, which is a d -amino acid-substituted pPorA peptide derived from the porin PorACj of Corynebacterium jeikeium , could form a stable monodisperse octameric pore 116–118 (Fig. 5(b)).…”
Section: Sensors Of Molecular Robotsmentioning
confidence: 99%
“…Redesigned peptide nanopores have demonstrated that such transmembrane peptides stably form pores with a certain number of monomers, opening the field of peptide nanopores and providing promising nanopore-forming peptides to date. Recently, the Mahendran group reported that DpPorA, which is a d -amino acid-substituted pPorA peptide derived from the porin PorACj of Corynebacterium jeikeium , could form a stable monodisperse octameric pore 116–118 (Fig. 5(b)).…”
Section: Sensors Of Molecular Robotsmentioning
confidence: 99%
“…Recently, advanced computational designs , and the modulation of natural assemblies have been exploited to build functional transmembrane structures . We recently presented the first report of a large functional and ion-selective α-helical nanopore made from the self-assembly of synthetic peptides based on the natural PorACj assembly. , In addition to their facile synthesis and autonomous assembly, these pores could be exploited for the charge-selective sensing of charged cyclic sugars and polypeptides …”
Section: Introductionmentioning
confidence: 99%
“…28,29 In addition to their facile synthesis and autonomous assembly, these pores could be exploited for the charge-selective sensing of charged cyclic sugars and polypeptides. 30 The nanopore approach has also extended beyond stochastic sensing and sequencing applications. 3,31 For example, covalent chemical reactions occurring on the interior walls of biological nanopores have been characterized at the single-molecule level with high temporal resolution.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2021, 12, 639−649. 3 The work highlighted the possibility of using synthetic α-helical pores for chargeselective sensing of polypeptides. • Krishnan, R. S.; Jana, K.; Shaji, A. Mahendran, K. R. Assembly of transmembrane pores from mirror-image peptides.…”
mentioning
confidence: 99%